An Introduction to a New Space Debris Evolution Model: SOLEM. (6th May 2019) - Wang, Xiao-wei; Liu, Jing
Abstract : SOLEM is the first space debris long-term evolution model of China. This paper describes the principles, components, and workflow of the SOLEM. The effects of different mitigation measures based on SOLEM model are analyzed and presented. The limitation of the model is pointed out and its future improvement work-plan is prospected.